Elevated Serum ADA Activity as a Marker for Diagnosis and Prognosis of Visceral Leishmaniasis and Post Kala-Azar Dermal Leishmaniasis in Indian Patients. - Vijayamahantesh; Ajay Amit; Manas R Dikhit; Raj K Pandey; Kuljit Singh; Ritesh Mishra; V N R Das; Pradeep Das; Sanjiva Bimal (PLoS ONE)
Serum adenosine deaminase (ADA) activity increases in diseases where cellular immunity is involved. Since cell-mediated immune responses play a paramount role in the pathogenesis and healing of the visceral leishmaniasis, therefore, the present study was undertaken to evaluate the serum ADA activity in different pathological conditions. Adenosine deaminase was determined in sera of active visceral leishmaniasis (VL) patients (n = 39), active postkala-azar dermal leishmaniasis (PKDL) cases (n = 34) at the point of diagnosis and after treatment stages along with healthy controls (n = 30), endemic healthy subjects (n = 34) and endemic asymptomatic subjects (n = 34).Our in-vitro result revealed that monocytes secrete significant ADA level in response to Leishmania donovani (L.donovani) stimulation. The serum ADA activity in active VL and PKDL subjects were found to be significantly higher than that of respective treated cases and healthy controls. We also observed a marginal number (17.6%) of endemic asymptomatic subjects showed elevated serum ADA activity. Further, the ADA activity in PKDL was found to be decreased gradually during the different phases of treatment. Interestingly, 2 out of 32 treated VL cases found to have high serum ADA activity during follow up period were relapsed within few days. These results suggest the possibility of ADA as a marker of clinical pathogenesis and can be used as a surrogate marker in the diagnosis and prognosis of VL and PKDL.